Let them rot : Antigone's parallax - Zupančič, Alenka (Idiom (Fordham University Press), 2023)
"A provocative, highly accessible journey to the heart of Sophocles' Antigone elucidating why it keeps resurfacing as a central text of Western thought and Western culture. Let Them Rot is Alenka Zupančič's absorbing and succinct guided tour of the philosophical and psychoanalytic issues arising from the Theban trilogy. Her original and surprising intervention into the broad and prominent field of study related to Sophocles' Antigone illuminates the classical text's ongoing relevance and invites a wide readership to become captivated by its themes."--